Sistem Pendukung Pariwisata Berkelanjutan yang Cerdas Menggunakan Metode AHP Sebagai Rekomendasi Pembangunan Desa Wisata Berkelanjutan - Kusumawardhani, Yuviani; Kurniawan, Taufik; Hariani, Dina (Jurnal Ilmiah Pariwisata, 2024)
SSustainable tourism in Indonesia is needed to see the high environmental degradation so that the worst impact causes a decrease in quality, especially in natural tourist destinations in rural areas. The government has made various efforts to implement sustainable tourism, one of which is through the sustainable tourism village certification programme. Currently, only 0.21% of tourist villages have been successfully certified. One of them is West Java Province, which only has 1 certified tourist village, namely Batulayang tourist village in Bogor Regency. Bogor Regency has the largest percentage of pilot tourism villages, which is 12.6% compared to other regions in West Java. This gap is an indication that there is an urgency to conduct deeper research related to the problem of uneven sustainable tourism in the tourist village of Bogor Regency. The purpose of this research is to build a tourism system through a digital platform (smart sustainable tourism) to make it easier for tourism village stakeholders to know and measure the priority of which indicators or indices for improvement so that in the future a sustainable tourism village will be created through appropriate technology. This research method uses a quantitative approach carried out using AHP (Analysis Hieararchy Process) with delphi method. The approach is carried out in order to determine the weight on each indicator that becomes the benchmark for sustainability in tourist villages. Keywords: communication, tour guide, tourist satisfaction, interaction